2018
DOI: 10.15666/aeer/1605_69636976
|View full text |Cite
|
Sign up to set email alerts
|

Nexus of Agriculture, Gdp, Population and Climate Change: Case of Some Eurasian Countries and Turkey

Abstract: Climate has an important role in the life processes of living creatures economically, socially and biologically. It affects several sectors and is affected by several sectors. Climate events are known to have changed since the second millennium and today it stands out as a problem that humanity has to face. Climate change has to be evaluated together with the global warming phenomenon. The most important factor causing global warming is the CO2 concentration. This study examines the effects of variables includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…This rise in land under cereal crops will enhance the productivity of the agriculture sector in lower-middle-income countries. This nding is in line with the results reported by other researchers in the literature (Dogan, 2018;Ahsan et al, 2019). However, the estimated long-run coe cient of the rural population is (-0.184), and the pvalue is (0.220), which shows that the association between the rural population and cereal production is negative and insigni cant.…”
Section: Resultssupporting
confidence: 93%
“…This rise in land under cereal crops will enhance the productivity of the agriculture sector in lower-middle-income countries. This nding is in line with the results reported by other researchers in the literature (Dogan, 2018;Ahsan et al, 2019). However, the estimated long-run coe cient of the rural population is (-0.184), and the pvalue is (0.220), which shows that the association between the rural population and cereal production is negative and insigni cant.…”
Section: Resultssupporting
confidence: 93%
“…There is a need to find and use low carbon footprint materials in buildings [10]. The total carbon emission in buildings is classified into embedded carbon and operational carbon emissions [11]. This embedded carbon emission is represented as emission by the material used in construction; operational emissions are produced by the activities of a human consuming the electricity by using home appliances [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many unit root tests are used in practice to investigate the stationarity of a series. The first-generation tests developed by Maddala and Wu ( 1999 ), Levin et al ( 2002 ), Hadri ( 2000 ), Choi ( 2001 ), and Im et al ( 2003 ) can be shown as an example of unit root tests (Doğan 2018 ).…”
Section: Materıal and Methodsmentioning
confidence: 99%
“…Information criteria such as AIC, SC, FPE, and HQ are used to determine the lag length. Here, the lag length that provides the smallest critical value is determined as the lag length of the model (Doğan 2018 ).…”
Section: Materıal and Methodsmentioning
confidence: 99%